2022
DOI: 10.3390/antiox11091652
|View full text |Cite
|
Sign up to set email alerts
|

Optimal DL-Methionyl-DL-Methionine Supplementation Improved Intestinal Physical Barrier Function by Changing Antioxidant Capacity, Apoptosis and Tight Junction Proteins in the Intestine of Juvenile Grass Carp (Ctenopharyngodon idella)

Abstract: The present study was a part of a larger research project that aimed to investigate the effects of Met-Met supplementation on fish growth and intestinal health. This study mainly focused on the relationship between dietary Met-Met and intestinal physical barrier function in fish. Seven iso-nitrogenous diets supplemented with 2.50 g/kg DL-methionine (DL-Met) and six graded levels of Met-Met (0.00, 0.79, 1.44, 1.84, 2.22, and 2.85 g/kg) were used to feed juvenile grass carp for 10 weeks, after which a 14-day Aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Because the physiological role of BAX is to maintain cell and tissue homeostasis, any dysregulation of BAX results in abnormal cell death [ 56 ]. It has been previously reported that some species of Aeromonas are able to induce the overexpression of proinflammatory cytokines, chemokines, and genes related to apoptosis [ 33 , 57 ], as we have observed with the strains studied in this work. In some cases, this overexpression is maintained during infection and is partially responsible for cytokine storm, a systemic inflammatory response that increases the infection severity [ 58 ].…”
Section: Discussionsupporting
confidence: 85%
“…Because the physiological role of BAX is to maintain cell and tissue homeostasis, any dysregulation of BAX results in abnormal cell death [ 56 ]. It has been previously reported that some species of Aeromonas are able to induce the overexpression of proinflammatory cytokines, chemokines, and genes related to apoptosis [ 33 , 57 ], as we have observed with the strains studied in this work. In some cases, this overexpression is maintained during infection and is partially responsible for cytokine storm, a systemic inflammatory response that increases the infection severity [ 58 ].…”
Section: Discussionsupporting
confidence: 85%
“…The reason may be that short-chain fatty acids (Qiao, 2020) or other prebiotics are produced during the fermentation process of AM, which promotes the growth of beneficial bacteria, inhibits harmful bacteria, improves the homeostasis of intestinal environment, and thus facilitates the development of intestinal mucosa (Cheng et al, 2021). The improvement of intestinal morphology enhances the intestinal barrier function, improves the immune and pathogenic microbial defense ability, and may reduce intestinal cell apoptosis (Wu et al, 2022a), and ultimately has a positive impact on the body's nutrient utilization and growth (Yang et al, 2022). The intestinal microbiota of fish is essential for maintaining the health of aquatic animals (Wang et al, 2021b).…”
Section: Figurementioning
confidence: 99%
“…Te pathogenesis of UC is closely linked to the intestinal barrier, intestinal fora, and immunity. Te intestinal barrier composed of intestinal epithelial cells and tight junctions (TJ) is the frst defensive site for the invasion of toxoid and pathogenic bacteria, and if the intestinal epithelial cells and TJ are disrupted, excessive oxidative stress and infammatory reactions can be induced, leading to the deterioration of UC [6,7]. Research has found that Agaricus blazei Murrill polysaccharides attenuate dextran sulfate sodium (DSS)induced colitis and protect the colon barrier from damage by decreasing MDA, TNF-α, IL-1β, and IL-6 levels and elevating SOD and IL-10 levels [8].…”
Section: Introductionmentioning
confidence: 99%